REVITILIZING THE ONTARIO PUBLIC EDUCATION SYSTEM FOR YOUNG ENGLISH LANGUAGE LEARNERS - Thomas G. Ryan; Kathryn Deuerlein (Informascope, 2018)
Herein we argue that teachers who work to foster their ability to teach English language learners effectively need to learn about their students. Although Ontario (Canada) educators have demonstrated that English language learners' cultural knowledge and language abilities can be mobilized within the classroom as important tools and resources for learning the systematic development of language policy at the school level is crucial for extending innovative practices and attitudes into schools across the province.  Such policy should reflect the demographic trends and recent research literature that recommends teachers must be informed and able to assess and evaluate English proficiency since this can disguise and hinder students from communicating the information they know.  Teachers, therefore, must be diligent and perceptive to accurately measure and record information that the student does know. Given this stance we present a review of the perspectives and attitudes of Ontario Elementary school teachers towards skills, abilities, and training for teaching young English language learners.  We introduce current themes and facts prevalent in the OMOE literature pertaining to effective ELL education and professional development for teachers to implement and foster English acquisition and student success.